2003
DOI: 10.1007/s11661-003-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chromium nitride and secondary austenite precipitation in duplex stainless steels

Abstract: A detailed investigation of the early stages of secondary austenite precipitation in five duplex stainless steel (DSS) commercial alloys (UNS S32304, S32205, S32550, S32750, and S32760) has been conducted using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Based on this study, a model is proposed that describes the interaction between Cr 2 N and austenite (intergranular and intragranular) precipitation in these alloys. Depending on nitrogen availability and interface mobility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
4
25

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(194 citation statements)
references
References 15 publications
9
156
4
25
Order By: Relevance
“…These precipitates resulted in depletion in Cr in the adjacent matrix region. The chromium-depleted zones provide a favorable site for pitting corrosion nucleation, as reported by several authors 6,8,9,14,20,23,[28][29][30][31][32] .…”
Section: Electrochemical Behaviorsupporting
confidence: 52%
See 1 more Smart Citation
“…These precipitates resulted in depletion in Cr in the adjacent matrix region. The chromium-depleted zones provide a favorable site for pitting corrosion nucleation, as reported by several authors 6,8,9,14,20,23,[28][29][30][31][32] .…”
Section: Electrochemical Behaviorsupporting
confidence: 52%
“…It is noteworthy that this type of austenite formed in the temperature range 800-1000°C and it is derived by dissolving Cr 2 N precipitates, which provides nitrogen to the formation of γ 2 23 , and its nucleation originates in inclusions and dislocations 23 . The HAZ exhibited chromium nitrides mainly in the interior of the ferrite grains.…”
Section: Microstructurementioning
confidence: 99%
“…δ and γ grains in fusion zones of all weldments were analyzed using EDX to examine the solute distribution in aswelded structure. High-cooling-rate caused suppression of solute redistribution in FZ and partially melted zone (PMZ) of GMA weldment [22], where Cr-rich precipitates were observed either in δ grains or at δ/δ or δ/γ grain boundaries (Figure 7). Nilsson and Wilson [2] and Kokawa et al [23] characterized these precipitates as Cr 2 N and reported that the hydrogeninduced cracking susceptibility increased as the density of these precipitates increased in the material.…”
Section: Microstructurementioning
confidence: 99%
“…Secondary austenite (γ 2 ) can also be formed during thermal treatments. The precipitation can occur at ferrite/ferrite grain boundaries, as chromium nitrides particles, in association to sigma phase as divorced eutectoid (δ→γ 2 +σ), or even due to the growing of primary austenite 7,8 . Besides γ 2 and σ, the chi phase (χ) may also be formed in Mo containing steels heated in the 700 -900 °C range 9,10 .…”
Section: Introductionmentioning
confidence: 99%